Marriage of the same Surname In Mandailing Batak Traditions In Padang Sidimpuan City - Gema Rahmadani; Yulia Yulia (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
Marriage within the same clan is prohibited in Batak tradition because individuals from the same clan are regarded as siblings who share a common ancestral lineage. In customary law, there are three marriage systems, namely exogamy, endogamy, and eleutrogamy. The Batak community adheres to an exogamous marriage system, which prohibits men and women from marrying individuals who belong to the same clan. Marriage within the same clan constitutes an important and interesting issue to examine because the Batak people consider such marriages as violations of customary values, social norms, and kinship structures that have been preserved for generations. Despite the existence of customary prohibitions and social sanctions, same-clan marriages continue to occur in contemporary society. For instance, in Padangsidimpuan City, several couples have entered into marriages within the same clan. This phenomenon indicates a shift in social values and raises questions regarding the effectiveness of customary sanctions, the influence of modernization, individual rights, religious perspectives, and changing patterns of social interaction in Batak society. Therefore, this study aims to analyze the factors underlying the occurrence of same-clan marriages, examine the customary sanctions imposed on such marriages, and explore the perspectives of the Batak community toward these practices. Furthermore, this research seeks to understand the dynamics between customary law and contemporary societal developments. The findings are expected to contribute to the development of customary law studies, particularly regarding the transformation of traditional values within modern Batak society and the sustainability of customary norms amid social change.